2008
DOI: 10.1520/jai101121
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Water Chemistry and Composition on Microstructural Evolution of Oxide on Zr Alloys

Abstract: The microstructure of oxide films formed on Zircaloy-4 and Alloy No. 3, which has a composition similar to ZIRLO™, was investigated by high resolution transmission and scanning electron microscopy, and by scanning probe microscopy after corrosion tests performed at 360°C/18.6 MPa in deionized water or lithiated water with 0.01 M LiOH. The microstructural evolution of the oxide films was analyzed by comparing the microstructure at different depths in the oxide layer. The defects, consisting of vacancies and int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…TEM and scanning electric microscope (SEM) techniques were employed to examine the microstructure and the fracture surface morphology of the oxide film covered on the Zircaloy-4 specimens corroded in lithiated water and deionized water at 633 K/18.6 MPa by Zhou et al [11,12]. Their results showed that more pores and microcracks formed along the grain boundaries in the oxide film covered on the specimens corroded in lithiated water than that corroded in deionized water.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…TEM and scanning electric microscope (SEM) techniques were employed to examine the microstructure and the fracture surface morphology of the oxide film covered on the Zircaloy-4 specimens corroded in lithiated water and deionized water at 633 K/18.6 MPa by Zhou et al [11,12]. Their results showed that more pores and microcracks formed along the grain boundaries in the oxide film covered on the specimens corroded in lithiated water than that corroded in deionized water.…”
Section: Resultsmentioning
confidence: 99%
“…So, the gathering of defects in the grain boundaries of the ZrO2 formed on the Zircaloy-4 specimen corroded in lithiated water could have been easier than that corroded in deionized water. Scanning probe microscopy (SPM) was employed to examine the surface morphology of the oxide covered on the specimens corroded in lithiated water in the early stage of pretransition [11]. Based Based on the discussion in the introduction, we know that the mechanism of the Li ions' effect on the surface energies of the grain boundaries of the oxide is more reasonable than others.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The oxidation of alloying elements dissolved in α-Zr on the corrosion resistance of alloys has dispersive effect than that of SPPs; Moreover, Bi dissolved in α-Zr can be more likely to dissolve in ZrO 2 than the Bi in SPPs, which can reduce the decrease of surface free energy due to the infiltration of oxygen ions and hydroxide ions. Therefore, the vacancy in the oxide film cannot easily diffuse and condense to form the pore-clusters and cracks, and the corrosion resistance of zirconium alloys can be improved [21].…”
Section: Discussionmentioning
confidence: 99%
“…Experimental and computed corrosion in an autoclave according to the data in[10] (E),[18] (B),[19] (C),[20] (a).…”
mentioning
confidence: 99%